Legal Challenges in Marine Governance in the North Natuna Marine Dispute Area - Kosho, Philippa Philomena; Rantung, Esterlita Nova Yaser (Fakultas Hukum Universitas Pattimura, 2026)
Introduction: The North Natuna Sea is rich in natural resources but remains a disputed area due to China’s nine-dash line claim, which overlaps with Indonesia’s EEZ under UNCLOS 1982.Purposes of the Research: The purpose of this study is to analyze Indonesia’s legal position and dispute resolution strategies in the North Natuna Sea.Methods of the Research: This research uses a normative juridical method by analyzing international legal instruments and national regulations related to EEZ and the law of the sea.Results of the Research: The findings show that Indonesia has a strong legal standing over its EEZ in the North Natuna Sea based on UNCLOS 1982. However, enforcement faces challenges such as unilateral claims, illegal foreign vessel activities, limited surveillance capacity, and weak dispute resolution mechanisms. A comprehensive strategy combining legal action, diplomacy, and strengthened economic presence is needed to uphold sovereignty and sustainably manage marine resources.